Synthesis and characterization of manganese dioxide nanoparticles and thin films - Wong, Catherine Chew Ling (Universiti Malaysia Sarawak, UNIMAS, 2007)
Stable colloidal suspensions of manganese dioxide were synthesized using different synthesis approaches. The first synthesis approach was by reducing KMnO4 with Na2S2O3 in stoichiometric ratio. The second synthesis approach involved redox reaction between stoichiometric amount of reagents KMnO4 and MnSO4 at high pH. The third synthesis approach involved mixing (1:1) molar ratio of the colloidal suspensions prepared by synthesis approach one and two. The manganese concentrations of manganese dioxide colloidal suspensions prepared by first, second and third synthesis approaches were determined by AAS to be 2.65 mg/L, 1.06 mg/L, and 1.45 mg/L respectively. UV-VIS spectra showed two major absorption peaks around 215 nm and 360 nm. These peaks were shifted to higher wavelength and lower energy indicating the formation of larger particles or aggregates upon aging for 30 days. The λmax of dialyzed manganese dioxide colloidal suspension was slightly lower than non-dialyzed manganese dioxide colloidal suspension indicating the relatively smaller particle size. The thin films of manganese dioxide were prepared by drop coating the freshly prepared colloidal suspension directly onto cleaned stainless steel plates. The total manganese dioxide loading of manganese dioxide thin films were 5.03 x 10-3 mg/cm2, 2.71 x 10-3 mg/cm2, and 3.48 x 10-3 mg/cm2 for synthesis approach one, two and three respectively. SEM micrographs showed that the manganese dioxide thin films were generally nanoparticulate and porous in nature. Studies by cyclic voltammetry (CV) showed that the manganese dioxide thin films from both synthesis approaches one and two exhibited good capacitative behaviors in aqueous 0.1M Na2SO4 electrolyte.